Secondary NAD+ deficiency in the inherited defect of glutamine synthetase. Issue 6 (21st April 2015) - Hu, Liyan; Ibrahim, Khalid; Stucki, Martin; Frapolli, Michele; Shahbeck, Noora; Chaudhry, Farrukh A.; Görg, Boris; Häussinger, Dieter; Penberthy, W. Todd; Ben‐Omran, Tawfeg; Häberle, Johannes
Abstract: Glutamine synthetase (GS) deficiency is an ultra‐rare inborn error of amino acid metabolism that has been described in only three patients so far. The disease is characterized by neonatal onset of severe encephalopathy, low levels of glutamine in blood and cerebrospinal fluid, chronic moderate hyperammonemia, and an overall poor prognosis in the absence of an effective treatment. Recently, enteral glutamine supplementation was shown to be a safe and effective therapy for this disease but there are no data available on the long‐term effects of this intervention. The amino acid glutamine, severely lacking in this disorder, is central to many metabolic pathways in the human organism and is involved in the synthesis of nicotinamide adenine dinucleotide (NAD + ) starting from tryptophan or niacin as nicotinate, but not nicotinamide. Using fibroblasts, leukocytes, and immortalized peripheral blood stem cells (PBSC) from a patient carrying a GLUL gene point mutation associated with impaired GS activity, we tested whether glutamine deficiency in this patient results in NAD + depletion and whether it can be rescued by supplementation with glutamine, nicotinamide or nicotinate. The present study shows that congenital GS deficiency is associated with NAD + depletion in fibroblasts, leukocytes and PBSC, which may contribute to the severe clinical phenotype of the disease. Furthermore, it shows that NAD + depletion can be rescued by nicotinamide supplementation in fibroblasts and leukocytes, which may open up potential therapeutic options for the treatment of this disorder.